PENGGUNAAN METODE MENULIS BERDASARKAN URUTAN UNTUK MENINGKATKAN KEMAMPUAN MENULIS AKSARA MANDARIN PADA SISWA SMA - Sari, Dewi Nurindah; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractWhen learning Chinese, many students find it difficult, especially writing Chinese characters. Mandarin characters are part of teaching Chinese as a foreign language. For students, Mandarin characters must be mastered in learning Mandarin. But Mandarin characters are very difficult to recognize, hard to write, hard to remember are facts. Even though they had studied for a year and a half, but at the time of his teaching, the teacher found many mistakes when writing Chinese characters, especially in the scratches and scratches. So, the author conducted a study in DARUL ULUM high school class XI with writing method based on sequence. From the results of the analysis, get the conclusion: the use of sequential writing methods to improve the ability to write the stroke sequence of the Chinese characters of DARUL ULUM students. After teaching, using the method of writing based on sequences can improve the ability to write the stroke of Chinese characters of DARUL ULUM students by 46.8%Keywords: Method Based On Sequence, Sequence Of Scratches, Writing Skills